Removal of Ion Nitrate and Phosphate Using Cocoa Shell Skin Modified With Functional Polymer - Aster Rahayu; Nafira Alfi Zaini Amrillah; Nuraini Nuraini; Veranica Veranica; Siti Jamilatun (Elkawnie, 2023)
Abstract: Cocoa is a plant that is widely cultivated in Indonesia, one of which is in the Yogyakarta area. On the outside of the cocoa fruit, it is known as the cocoa shell skin. Cocoa shell skin is an agricultural waste that is a simple, cheap, and environmentally friendly development that is used as an adsorbent for nitrate and phosphate removal. This article discusses the observation of the ability of the cacao shell against ion nitrate and phosphate adsorption and then compares it after being modified with a functional polymer. Modification of the surface of cacao shell skin with 2-[(methacryloyloxy)ethyl]trimethylammonium chloride (META) resulted in an improvement; the percentages of removal of ion nitrate and phosphate were 89.67% and 92%, respectively. In addition, this study compared the characterization of materials resulting from the absorption of Cocoa Shell Skin (CH) and Cocoa Shell Skin Modified META (CH-META) for nitrate and phosphate ions using Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). The modification with META could improve the C-N group and N-H groups on the surface of cacao shell skin. Abstrak: Kakao merupakan tanaman yang banyak dibudidayakan di Indonesia salah satunya di daerah Yogyakarta. Bagian luar buah kakao dikenal dengan kulit cangkang kakao. Kulit cangkang kakao merupakan limbah pertanian yang merupakan pengembangan sederhana yang murah dan ramah lingkungan serta digunakan sebagai adsorben penyerap nitrat dan fosfat. Artikel ini membahas tentang observasi kemampuan kulit cangkang kakao terhadap adsorpsi ion nitrat dan fosfat kemudian adanya perbandingan dengan cangkang cacao setelah dilakukan modifikasi dengan polimer fungsional. Modifikasi permukaan kulit cangkang kakao dengan META menghasilkan peningkatan persentase penyerapan ion nitrat dan fosfat masing-masing sebesar 89,67% dan 92%. Selain itu, penelitian ini membandingkan karakterisasi bahan hasil penyerapan Cocoa Shell Skin (CH) dan Cocoa Shell Skin – Modifikasi META (CH-META) untuk ion nitrat dan fosfat menggunakan Fourier-Transform Infrared (FTIR) dan Scanning Electron Microscopy (SEM). Modifikasi dengan META dapat meningkatkan gugus C-N dan gugus N-H pada permukaan kulit cangkang kakao.